THU0455 Renal safety of lesinurad: a pooled analysis of phase iii and extension studies. (15th June 2017) - Terkeltaub, R; Malamet, R; Bos, K; Li, J; Goldfarb, DS; Pillinger, M; Jalal, D; Hu, J; Saag, K
Abstract : Background: Lesinurad (LESU) is a selective uric acid reabsorption inhibitor approved in the United States and European Union at a 200 mg daily dose in combination with a xanthine oxidase inhibitor (XOI) for treatment of hyperuricemia associated with gout in patients unable to achieve target serum uric acid on an XOI (allopurinol or febuxostat) alone. Objectives: To investigate the renal safety of LESU, data were pooled from 3 pivotal, placebo-controlled, 12-month phase III (core) studies evaluating lesinurad 200 mg (LESU200) and 400 mg (LESU400) in combination with an XOI and from 2 extension studies, where patients continued LESU+XOI at the same dose or were randomized from placebo to LESU200 or LESU400 plus an XOI. Methods: Renal-related and kidney stone safety data were pooled from core studies to compare LESU200+XOI and LESU400+XOI with an XOI alone and from core studies + extension studies to evaluate the impact on renal safety of extended LESU+XOI treatment. Renal-related treatment-emergent adverse events (TEAEs) were a customized list of 36 preferred terms selected from the Medical Dictionary for Regulatory Activities (MedDRA) Renal and Urinary Disorders System Organ Class (SOC), the Investigations SOC, and the Acute Renal Failure MedDRA Standardized MedDRA Query (SMQ). Descriptive statistics are provided for patients receiving ≥1 dose of study medication. To adjust for varying treatment duration, TEAEs are expressed as exposure-adjusted incidence rates (EAIRs; number of subjects with events per 100 person-years). Results: In the core studies, EAIRs for any renal-related TEAE, serious renal-related TEAEs, and renal-related TEAEs leading to discontinuation were similar with an XOI alone and LESU200+XOI and lower than with LESU400+XOI (Table 1 ). Similar results were found for kidney stone and serious kidney stone TEAEs. The most common renal-related TEAE was increased serum creatinine (sCr). EAIRs for sCr elevations ≥1.5x baseline were higher with LESU+XOI than XOI alone (Table 1 ). Overall, 75% and 84% of sCr elevations in the XOI alone and LESU+XOI groups, respectively, were resolved at last study assessment; 75% and 66% resolved without interruption of medication. Exposure to extended LESU+XOI treatment in the core+extension studies did not show an increase from core studies in EAIRs for any renal-related or kidney stone adverse event category (Table 2). Conclusions: Lesinurad at the approved dose of 200 mg once daily combined with XOI demonstrated comparable rate of adverse events to XOI alone. There was no clinically relevant increase in these adverse events with the extension of treatment beyond 1 year. Acknowledgements: This study was funded by Ardea Biosciences/AstraZeneca. Disclosure of Interest: R. Terkeltaub Consultant for: Ardea Biosciences/AstraZeneca, SOBI, Horizon, Revive, Aequus, Relburn, Selecta, ProteoThera, R. Malamet Employee of: AstraZeneca, K. Bos Employee of: AstraZeneca, J. Li Employee of: AstraZeneca, D. Goldfarb Consultant for: AstraZeneca, Revive, Cymabay, Retrophin, M. Pillinger Grant/research support from: Takeda, Consultant for: AstraZeneca, Crealta/Horizon, D. Jalal: None declared, J. Hu Employee of: Ardea Biosciences, K. Saag Consultant for: Ardea/AstraZeneca, Horizon, Takeda